Improving the educational system for children with disabilities. - Usmonova Muxlisaxon Sobirovna (Peerian Journals Publishing, 2022)
This article discusses ways and means of further improving the education system in the field of education of children with disabilities, as well as work with children with disabilities.
Keywords: Education; inclusive education; integrated; corrective